Education for Democracy in the Republic Of Serbia - Minić, Vesna Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Considering to the fact that democracy, especially in the societies in transition, today has become the key question of their functioning and development, the discussion about this question have different reasons. The school as the educational institution in Serbia has numerous and responsible tasks in founding and developing of democratic relationships, mutual relations of the tolerance, respecting, peaceful solutions ect. By acquiring of needed knowledge and democratic values, students become competent for living with social differences, for taking responsibility and active functioning which is directed to the constructive way. Democracy is not just the form of political system, but also the mean for realizing of practical goals. Democratic consciousness and knowledge are mostly acquired in schools, in which the specific way of thinking, communication and readiness for practical acting are developing and that is the precondition for education for democracy. But, it is important to understand democracy in the proper way, because it is not meaning the absolute freedom, but respecting of rules and obligations which means harmonious living in the given social environment. Democratization in the Republic of Serbia is connected to the general process of globalization and appearing of new values such as tolerance, solidarity, personal rights ect. In school, it means learning about dialog and tolerance. Beside, it prepares students for living and working in democratic society, that is learning about democratic values, forming attitudes about and making the environment in which they can take participance in some social activities related to democratic relationships in school. By democratic knowledge and values, the student can learn about living in social, cultural and political differences, in conflict of interests, about taking of rights and obligations, taking of responsibility for decisions in which making one is taking part. Education for democracy is different in the consist of different educational subjects, between which the civil education has the greatest importance. Its goal is the preparation of students for active participation in the process of education, developing of values and abilities which are needed for forming of responsible person who is cooperative and respective for himself and others.